Diamagnetically levitated nanopositioners with large-range and multiple degrees of freedom - K. S. Vikrant; G. R. Jayanth (Nature Communications, 2022)
Precision positioning stages are often central to science and technology at the micrometer and nanometer length scales. Here, the authors report compact, diamagnetically levitated positioning stages that achieve large-range, six degrees-of-freedom positioning with nanometer-scale precision.